Merumuskan Hermeneutika Hadis Kontekstual Liberatif: Dialog Pemikiran Nashr Hamid Abu Zayd dan Farid Esack : - Nazilatul Widad; Masruhan Masruhan (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This article aims to formulate a model of contextual-liberative hadith hermeneutics through a dialogue between the thoughts of Nasr Hamid Abu Zayd and Farid Esack. This study departs from the problem of literalist, rigid, and ahistorical readings of hadith, which often fail to adequately respond to contemporary human issues such as social injustice, poverty, gender inequality, discrimination, and the marginalization of vulnerable groups. This research employs a qualitative method based on library research, utilizing comparative analysis and conceptual synthesis. Primary data are derived from Abu Zayd’s major works, particularly Mafhum al-Nass and Ishkaliyyat al-Qira’ah wa Aliyyat al-Ta’wil, as well as Farid Esack’s writings, notably Qur’an, Liberation and Pluralism and On Being a Muslim. Secondary data are obtained from indexed journal articles and relevant academic books. The findings indicate that Abu Zayd offers methodological contributions through his historical-linguistic approach, incorporating the concepts of dalālah, maghzā, and maskūt ‘anhu, while Esack provides ethical-liberative contributions based on the principles of tawḥīd, taqwā, al-nās, al-mustaḍ‘afūn fī al-arḍ, ‘adl-qisṭ, and jihād. This article concludes that contextual-liberative hadith hermeneutics can serve as an integrative model that preserves the authenticity of the text while reconstructing the ethical significance of hadith in addressing modern humanitarian problems.